Evaluation of Post- Operative Sensitivity of Nano Filled Composite Versus Bulk Filled Resin Composite in Posterior Class 2 Restoration: Post- Operative Sensitivity of Nano Filled Composite - Channa, Sadia; Rajput, Fozia; Bilgrami, Afreen; Javed, Farhan; Faraz, Hira; Madiha, . (Pakistan Journal of Health Sciences, 2023)
Dental composites use adhesives to adhere and are thermally non-conductive. Despite advances in restorative dentistry, adhesive restorations may cause postoperative pain and fail. Objective: To compare and evaluate the post-operative sensitivity between nano resin composite using incremental technique and bulk filled resin composite using bulk filled technique in class 2 posterior restorations by assessing the post-operative pain and sensitivity. Methods: Two hundred and twenty patients who satisfied inclusion and exclusion criteria were lottery-divided into groups A and B. Nano resin composite was placed via incremental technique in Group A and bulk filled in Group B. Post-operative pain was assessed using Visual Analog Scale 0-10 at 24 hours and 7 days. Results: Male patients were 47 (42.7%) and 48 (43.6%), female patients were 63 (57.3%) and 62 (56.4%). Mean of pain was 2.39 ± 0.97 and 2.32 ± 0.81 at 24 hours postoperatively and 0.14 ± 0.63 and 0.00 at 7 days in group A and group B respectively. Pain level was mild in 97 (88.2%) and 105 (95.5%) patients, moderate in 13 (11.8%) and 5 (4.5%) after 24 hours, no pain in 105 (95.5%) and 110 (100.0%) and mild in 5 (4.5%) and 0 (0.0%) at 7 days in group A and group B, respectively. Conclusion: Bulk filled resin composite using bulk filled technique is more effective in class 2 posterior restorations as compared to nano resin composite using incremental technique